Nitrogen-Doped Carbon Coated WS2 Nanosheets as Anode for High-Performance Sodium-Ion Batteries - Liu, Yong; Wei, Huijie; Wang, Chao; Wang, Fei; Wang, Haichao; Zhang, Wanhong; Wang, Xianfu; Yan, Chenglin; Kim, Bok H.; Ren, Fengzhang (Frontiers in Chemistry, 2018)
Due to the cost-effectiveness of sodium source, sodium-ion batteries (SIBs) have attracted considerable attention. However, SIBs still have some challenges in competing with lithium-ion batteries for practical applications. Particularly, the high rate capability and cycling stability are posing big problems for SIBs. Here, nitrogen-doped carbon-coated WS2 nanosheets (WS2/NC) were successfully synthesized by a high-temperature solution method, followed by carbonization of polypyrrole. When used as anode electrodes for SIBs, WS2/NC composite exhibited high-rate capacity at 386 and 238.1 mAh g−1 at 50 and 2,000 mA g−1, respectively. Furthermore, even after 400 cycle, the composite electrode could still deliver a capacity of 180.1 mAh g−1 at 1,000 mA g−1, corresponding to a capacity loss of 0.09% per cycle. The excellent electrochemical performance could be attributed to the synergistic effect of the highly conductive nature of the nitrogen-doped carbon-coating and WS2 nanosheets. Results showed that the WS2/NC nanosheets are promising electrode materials for SIBs application.